The presence and prevalence of bovine parainfluenza 3 (BPIV-3), bovine papillomaviruses (BPV), bovine herpesvirus 1 (BHV-1) in subclinical mastitis in cattle - Altun, Serdar; Özdemir, Selçuk; Sağlam, Yavuz Selim (Afyon Kocatepe Üniversitesi)
In general, bacterial pathogens are the focus of mastitis studies. Symptoms of mastitis may be absent in cases of viral infection, because other clinical symptoms are more dominant. Subclinical mastitis cases cannot be generally diagnosed and as a consequence, they are not investigated very well. This may lead to the inability of viral agents to be predicted in bovine subclinical cases. There are many viral agents associated with bovine mastitis and which may cause subclinical mastitis in dairy cattle. However, since viral infections have not been much investigated in mastitis studies, strategies developed against subclinical mastitis may be inadequate. Bovine Parainfluenza 3 (BPIV-3), Bovine Papillomaviruses (BPV), Bovine Herpesvirus 1 (BHV-1) could cause clinical and subclinical mastitis. The aim of the present study was to investigate the presence and prevalence of BPIV-3, BPV, and BHV-1 viral agents in subclinical mastitis case in Erzurum province. For this purpose, 120 bovine mammary tissues with no macroscopic lesions were collected and these tissues were examined with histopathology and immunofluorescence methods. Thereafter, all viruses were identified with qRT-PCR in mammary tissues. The end of histopathologic process 78 of 120 cases (56 chronic subclinic mastitis, 22 acut mastitis) was found severity of inflammatory changes. According to the results of immunofluorescence staining for all sections. The immun positive signs for BPIV-3 BPV, and BHV-1 was determined in 50 out of 120 cases. qRT-PCR results which compatible with immunofluorescence results showed that BPIV-3 agent was detected by the qRT-PCR in 26/120 samples, BPV-2 agent in 8/120 samples, BHV-1 agent in 16/120 samples, and BPV-1 agent in 7/120 samples (only by qRT-PCR). Coinfection with BPIV-3 and BHV-1 was detected in 5/120 samples, BPIV-3, and BPV-1 in 3/120 samples, BHV-1, and BPV-2 in 2/120 samples. According to our results, although the role of viral agents in mastitis disease has not been clearly elucidated, we have found that viral agents are common in mammary tissues with subclinical mastitis.

Genellikle etiyolojik mastitis çalışmaları bakteriyel patojenler üzerine odaklanmıştır. Viral enfeksiyon vakalarında mastit belirtileri, diğer klinik semptomlar daha baskın olduğu için gözden kaçabilmektedir. Subklinik mastitis olguları genellikle teşhis edilemediği için çok iyi araştırılmamıştır. Bu durum sığır subklinik mastitis vakalarında viral ajanların önlenememesine yol açabilmektedir. Sığırlarda mastitis ile ilişkili ve süt sığırlarında subklinik mastite neden olabilecek birçok viral ajan tanımlanmıştır. Bununla birlikte, mastitis çalışmalarında viral enfeksiyonlar çok fazla araştırılmamış olduğundan, subklinik mastitislere karşı geliştirilen stratejiler yetersiz olabilir. Sığır Parainfluenza 3 (BPIV-3), Sığır papillomavirüsleri (BPV), sığır herpes virüsü 1 (BHV-1) klinik ve subklinik mastitlerde rol aldığı düşünülen viral ajanlardır. Bu çalışmada, Erzurum ilindeki subklinik mastitis olgularındaki BPIV-3, BPV ve BHV-1 viral ajanlarının varlığının ve prevalansının araştırılması amaçlanmıştır. Bu amaçla 120 büyükbaş hayvanın makroskobik olarak lezyon izlenmyen meme doku örnekleri toplandı ve bu dokular histopatoloji ve immünofloresan yöntemlerle incelendi. Ayrıca, meme dokularında belirlenen viral etkenlerin varlığı qRT-PCR ile araştırıldı. Toplanan 120 örneğe yapılan histopatolojik değerlendirme sonucunda (56 kronik mastit, 22 akut mastit) 78 örnekte yangısal değişikliklere rastlandı. Tüm dokulara uygulanan immünofloresan boyama sonuçlarına göre 120 olguda kronik mastitis tanısı konan 50 örnekte pozitif reaksiyonlara rastlandı. qRT-PCR sonuçlarına göre immunfloresan boyama sonuçlarıyla uyumlu olarak toplam 50 (%41.6) örnekte etkenlerin DNA varlıkları tespit edildi. BPIV-3 etkenine 26/120, BPV-2 etkenine 8/120, BHV-1 etkenine 16/120 oranında olduğu tespit edildi. Sadece qRT-PCR yöntemi kullanılarak 7/120 oranında BPV-1 etkenine rastlandı. Ayrıca, 5/120 oranında BPIV3 ve BHV-1, 3/120 oranında BPIV-3 ve BPV-1, 2/120 oranında ise BHV-1 ve BPV-2 etkenlerine birlikte rastlandı. Yapılan çalışmadan elde edilen sonuçlara göre, mastitis hastalığında viral ajanların rolü açık bir şekilde aydınlatılmamış olmakla birlikte, viral ajanların subklinik mastitli meme dokularında yaygın olduğunu tespit edilmiştir.
Sığırlarda subklinik mastitisde sığır parainfluenza 3 (BPIV-3), sığır papillomavirüsleri (BPV), sığır herpesvirüs 1 (BHV-1) varlığı ve prevalansı
Keywords: Subclinical Mastit; qRT-PCR; Bovine Parainfluenza 3; Bovine Papillomaviruses; Bovine Herpesvirus 1; Immunofluorescence